The path to [Formula omitted] parton distributions - Ball, Richard D; Barontini, Andrea; Candido, Alessandro; Carrazza, Stefano; Cruz-Martinez, Juan; Del Debbio, Luigi; Forte, Stefano (The European physical journal. C, Particles and fields, 2024)
We extend the existing leading (LO), next-to-leading (NLO), and next-to-next-to-leading order (NNLO) NNPDF4.0 sets of parton distribution functions (PDFs) to approximate next-to-next-to-next-to-leading order ( [Formula omitted]). We construct an approximation to the [Formula omitted] splitting functions that includes all available partial information from both fixed-order computations and from small and large x resummation, and estimate the uncertainty on this approximation by varying the set of basis functions used to construct the approximation. We include known [Formula omitted] corrections to deep-inelastic scattering structure functions and extend the FONLL general-mass scheme to [Formula omitted] accuracy. We determine a set of [Formula omitted] PDFs by accounting both for the uncertainty on splitting functions due to the incomplete knowledge of [Formula omitted] terms, and to the uncertainty related to missing higher corrections (MHOU), estimated by scale variation, through a theory covariance matrix formalism. We assess the perturbative stability of the resulting PDFs, we study the impact of MHOUs on them, and we compare our results to the [Formula omitted] PDFs from the MSHT group. We examine the phenomenological impact of [Formula omitted] corrections on parton luminosities at the LHC, and give a first assessment of the impact of [Formula omitted] PDFs on the Higgs and Drell-Yan total production cross-sections. We find that the [Formula omitted] NNPDF4.0 PDFs are consistent within uncertainties with their NNLO counterparts, that they improve the description of the global dataset and the perturbative convergence of Higgs and Drell-Yan cross-sections, and that MHOUs on PDFs decrease substantially with the increase of perturbative order.